2020
DOI: 10.1371/journal.pone.0229314
|View full text |Cite
|
Sign up to set email alerts
|

A micro-PRNT for the detection of Ross River virus antibodies in mosquito blood meals: A useful tool for inferring transmission pathways

Abstract: Introduction Many arboviruses of public health significance are maintained in zoonotic cycles with complex transmission pathways. The presence of serum antibody against arboviruses in vertebrates provides evidence of their historical exposure but reveals nothing about the vectorreservoir relationship. Moreover, collecting blood or tissue samples from vertebrate hosts is ethically and logistically challenging. We developed a novel approach for screening the immune status of vertebrates against Ross River virus … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 39 publications
4
5
0
Order By: Relevance
“…In an initial proof-of-concept time-course experiment, mosquitoes were held for set timepoints after blood-feeding on one negative control and two positive control volunteers to assess the detectability of the antibodies in the bloodmeal during mosquito digestion under normal insectary conditions. Consistent with previous studies on antibodies against other pathogens ( 13 16 , 27 , 28 ), antibodies against SARS-CoV-2 remained detectable at least 10 h after feeds, with a loss of signal seen between that timepoint and 24 h later (data not shown).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In an initial proof-of-concept time-course experiment, mosquitoes were held for set timepoints after blood-feeding on one negative control and two positive control volunteers to assess the detectability of the antibodies in the bloodmeal during mosquito digestion under normal insectary conditions. Consistent with previous studies on antibodies against other pathogens ( 13 16 , 27 , 28 ), antibodies against SARS-CoV-2 remained detectable at least 10 h after feeds, with a loss of signal seen between that timepoint and 24 h later (data not shown).…”
Section: Resultssupporting
confidence: 91%
“…Early experiments to evaluate the effect of time after feeding on antibody detection revealed that mosquitoes preserved in 80% ethanol indicated rapid reactivity degradation compared with those desiccated on silica gel (not shown). Both laboratory experiments in NIH and field studies in Mali confirmed earlier studies ( 13 , 15 , 16 , 27 , 28 ) that antibody detection persisted with minimal degradation until at least 10 h and degradation was evident at later timepoints (24–36 h after feeding) (see, for example, Figure 3 ). Since most Anopheles spp.…”
Section: Discussionsupporting
confidence: 83%
“…All 480 bloodmeal samples collected in this study were screened for the presence of anti-RRV antibodies using an adapted micro-PRNT 21 and more than half (n=243, 51%) were seropositive (Table 2). RRV seroprevalence was 52% (131/253) in humans, 70% in cattle and eastern grey kangaroos (21/30 and 14/20, respectively), and ranged from 25% to 100% in samples from other animals.…”
Section: Resultsmentioning
confidence: 99%
“…The analysis of the vertebrate host preferences of haematophagous arthropods, using molecular identi cation of bloodmeals is common practice and a key part of investigations on potential transmission pathways [17][18][19][20] , but only recently have bloodmeals also provided an opportunity to determine pathogen exposure in the host 21 . Screening for live virus in large mosquito collections is onerous and time consuming, and usually only a low detection rate is achievable 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Koala sera that neutralised ≥ 50% of plaques in these assays were considered anti-RRV seropositive 65 . This methodology has been deployed in a number of studies 66 , 67 , and has been tested at dilution rates of > 160 fold confirming strong and specific binding by the antibody 67 . We considered an animal sampled multiple times as seropositive if the animal returned a positive test result during any individual sampling event.…”
Section: Methodsmentioning
confidence: 99%